2021
DOI: 10.3390/diagnostics11020341
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNA as Biomarkers for Colorectal Cancer Diagnosis and Liver Metastasis

Abstract: Colorectal cancer (CRC) is the second leading cause of cancer deaths worldwide. Stage IV CRC patients have poor prognosis with a five-year survival rate of 14%. Liver metastasis is the main cause of mortality in CRC patients. Since current screening tests have several drawbacks, effective stable non-invasive biomarkers such as microRNA (miRNA) are needed. We aim to investigate the expression of miRNA (miR-21, miR-19a, miR-23a, miR-29a, miR-145, miR-203, miR-155, miR-210, miR-31, and miR-345) in the plasma of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 68 publications
2
28
0
4
Order By: Relevance
“…Examination of miRNAs for specific fractions can significantly increase both the sensitivity and specificity of selected circulating miRNAs as noninvasive biomarkers [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Circulating Mirnamentioning
confidence: 99%
“…Examination of miRNAs for specific fractions can significantly increase both the sensitivity and specificity of selected circulating miRNAs as noninvasive biomarkers [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Circulating Mirnamentioning
confidence: 99%
“…Similar to other miRNAs, miR-203's activity can be halted by means of sponging by ncRNAs, such as FBXL19-AS1 [236], BANCR [237], and LINC00657 [238]. Many studies into the serum/plasma levels of miR-203 in CRC patients have discovered that differential levels of miR-203 are most often an indicator of poor prognosis and increased metastasis usually marked by an increase in miR-203 [89][90][91][93][94][95][96], with some showing lowered levels [84,92]. A meta-analyses of 11 papers found a higher miR-203 expression in CRC tissue to be significant, and not in serum, but a combination of both serum and CRC tissue was predictive of a poor outcome [239].…”
Section: Mir-203mentioning
confidence: 99%
“…Additionally, several studies have indicated that blood samples have emerged as a reliable source of biomarkers [ 127 , 128 ]. Accordingly, cancer-related miRNAs, either CEx-miRNAs or cancer-derived cell-free miRNAs (cf-miRNAs), from blood represents a promising target for more accessible and non-invasive testing [ 129 , 130 ]. In this regard, blood CEx and miRNA extraction can be easily achieved through available commercial kits, delivering precise and valuable diagnostic and prognostic data [ 131 , 132 , 133 ].…”
Section: Cex-mirnas For Crc Diagnosismentioning
confidence: 99%